A study on section 75 of contracts act 1950: essentiality of proving 'actual loss' in effectuating construction liquidated damages clause / Akmyr Ahmad Azwan Abdul Kadir …[et al.] - Abdul Kadir, Akmyr Ahmad Azwan; Ramli, Aimi Nashirah; Mohd Adnan, Nur Afiqah Husna; Joudi, Fifiyani (2014)
Malaysia has been a successful developing country and is forging ahead to become a developed nation in its own mold. In order to be more successful, the internal development must progressively expand to be at par with international standing. Hence, it is vital for Malaysia to have an effective law governing the contractual relationship specifically in construction and employment fields. A major challenge it has to address in this endeavor is the uncertainties with regard to the application of liquidated damages pursuant to Section 75 of Contracts Act 1950. Basically, this research aims to identify whether actual loss needs to be proven before an aggrieved party can effectuate the provisional clause as laid in the contract. These aims is achieved by an adaptation of doctrinal and empirical research methodologies whereby all primary and secondary sources including legal books, journals, articles, cases, and also interviews with learned practical respondents from various legal fields. To impart thorough discussions and resolutions for this research, the application of liquidated damages in three different countries i.e., India, Singapore and Australia, are also reviewed. The outcome of this research shows that there is indeed a need for Section 75 to be amended or at the very least, the initial contractual terms itself should be re-evaluate so as to promote certainty. Thus, this research finding will indubitably regain the confidence of contracting parties dealing with liquidated damages and also will reduce the possibly of conflicts for the courts to resolved.